Amplification of the PLAG-family genes - PLAGL1 and PLAGL2 - is a key feature of the novel tumor type CNS embryonal tumor with PLAGL amplification - Keck, Michaela-Kristina; Sill, Martin; Stichel, Damian; Sievers, Philipp; Wefers, Annika K.; Sturm, Dominik; Schramm, Kathrin; Selt, Florian; Ecker, Jonas; Milde, Till; Deimling, Andreas von; Pfister, Stefan; et al. (Acta neuropathologica, 2023)
Pediatric central nervous system (CNS) tumors represent the most common cause of cancer-related death in children aged 0-14 years. They differ from their adult counterparts, showing extensive clinical and molecular heterogeneity as well as a challenging histopathological spectrum that often impairs accurate diagnosis. Here, we use DNA methylation-based CNS tumor classification in combination with copy number, RNA-seq, and ChIP-seq analysis to characterize a newly identified CNS tumor type. In addition, we report histology, patient characteristics, and survival data in this tumor type. We describe a biologically distinct pediatric CNS tumor type (n = 31 cases) that is characterized by focal high-level amplification and resultant overexpression of either PLAGL1 or PLAGL2, and an absence of recurrent genetic alterations characteristic of other pediatric CNS tumor types. ...
Online veröffentlicht: 27. November 2022
Gesehen am 06.12.2023